2003
DOI: 10.1177/1073858403253552
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in the Inhibitory Architecture of the Cell Minicolumn: Implications for Autisim

Abstract: The modular arrangement of the neocortex is based on the cell minicolumn: a self-contained ecosystem of neurons and their afferent, efferent, and interneuronal connections. The authors' preliminary studies indicate that minicolumns in the brains of autistic patients are narrower, with an altered internal organization. More specifically, their minicolumns reveal less peripheral neuropil space and increased spacing among their constituent cells. The peripheral neuropil space of the minicolumn is the conduit, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
241
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(262 citation statements)
references
References 66 publications
17
241
1
3
Order By: Relevance
“…Presently, it is unknown whether the increase in breastfeeding rates and duration in as-yet-undefined but genetically at-risk populations could be correlated with incidence of some developmental disorders such as autism spectrum disorders (ASD), language impairments, or attention disorders (58,59). Although to date no evidence exists to support such a scenario, our finding of an imbalance between excitation and inhibition, which is consistent with genetic (60-63), anatomical (64,65), and electrophysiological (66)(67)(68)(69) evidence of imbalance between excitation and inhibition as a core abnormality of autism, supports further investigations in this direction (70). Furthermore, it has been suggested that abnormal Ca 2ϩ signaling, resulting from genetics or environmental factors, may be linked to ASD (71) through disruptions of critical developmental signaling pathways important in regulating neuronal migration, differentiation, and synaptogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…Presently, it is unknown whether the increase in breastfeeding rates and duration in as-yet-undefined but genetically at-risk populations could be correlated with incidence of some developmental disorders such as autism spectrum disorders (ASD), language impairments, or attention disorders (58,59). Although to date no evidence exists to support such a scenario, our finding of an imbalance between excitation and inhibition, which is consistent with genetic (60-63), anatomical (64,65), and electrophysiological (66)(67)(68)(69) evidence of imbalance between excitation and inhibition as a core abnormality of autism, supports further investigations in this direction (70). Furthermore, it has been suggested that abnormal Ca 2ϩ signaling, resulting from genetics or environmental factors, may be linked to ASD (71) through disruptions of critical developmental signaling pathways important in regulating neuronal migration, differentiation, and synaptogenesis.…”
Section: Discussionsupporting
confidence: 79%
“…It has therefore been postulated that reduced neuropil space would limit the effectiveness of this inhibitory 'sheath', and lead to reduced neural inhibition in ASD (Casanova, Buxhoeveden, & Gomez, 2003). However, in contrast to the suggestion that narrower minicolumns in ASD are associated with reduced inhibition, computational modelling work (Gustafsson, 1997b) and experimental studies in cats (Hensch, 2007), have shown that in fact narrower minicolumns could be associated with increased inhibition.…”
Section: Cortical Minicolumnsmentioning
confidence: 88%
“…Gustafsson proposed that stronger lateral connectivity between adjacent minicolumns could predict enhanced sensory discrimination of simple stimuli and impaired global perception (referred as to increased lateral inhibition (Gustafsson 1997)). Physiological support for his hypothesis has come from neuropathological studies showing an atypical distribution of interneurons in autism (Casanova et al 2003;Casanova 2006). Essentially, increased lateral inhibition is an extrapolation of normal physiological processes that enhance resolution and contrast of perception.…”
Section: Discussionmentioning
confidence: 99%